Development and Validation of an LC-MS/MS Method for the Determination of Lamivudine, Tenofovir & Efavirenz in human plasma - Mounika V, Mounika V; Devi, Akila (Journal of Neonatal Surgery, 2025)
Introduction: Therapeutic drug monitoring of Lamivudine, tenofovir and efavirenz, three commonly used antiretroviral drugs, is important to maximize effectiveness while minimizing side effects. Materials and Methods: Chromatographic separation was done on Xterra, C18 (2), 150 X 4.6 mm, 5 µm column with a mobile phase composed of 10mM ammonium formate-methanol-acetonitrile in the ratio of 50:25:25 (v/v/v), at a flow rate of 1.0 mL/min. Turbo ion-spray interface (TIS) operated in positive ionization mode was used for the mass spectrometric detection. The MRM transitions monitored were m/z 230.1/112.1 (lamivudine), m/z 288.0/176.2 (tenofovir), m/z 316.2/168.1 (Efavirenz), m/z 248.1/130.1 (Emtricitabine,ISTD) and m/z 287.2/191.2(Abacavir,ISTD). The method was developed and the established calibration ranges are 10-3018 ng/mL, 5-500ng/mL and 20-6021ng/mLfor lamivudine, tenofovir disoproxilfumarateand efavirenz respectively. The slope values are consistent and regression values were found to be more than or equal to 0.99. The accuracy for run size reproducibility batch and dilution integrity (1/2, 1/4) for lamivudine, tenofovir disoproxilfumarateand efavirenz was found to be in the range of 96.9-102.2%. The precision was found to be less than 8.1% for three analytes. Further, the reported method was validated as per the ICH guidelines and found to be well with in the acceptable range. Results: The method showed good accuracy, low limits of quantification, adequate recovery, minimal matrix effects, and specificity. Analyte stability under multiple storage conditions was demonstrated. Conclusion: The validated LC-MS/MS method provides a reliable tool for therapeutic drug monitoring and pharmacokinetic studies of anti-HIV regimens. The assay can be applied to large populations, especially in resource-poor settings, to help individualize dosing and improve clinical outcomes while reducing toxicity